Acupuncture therapy for the treatment of stable angina pectoris: An updated meta-analysis of randomized controlled trials. (February 2019) - Liu, Yuan; Meng, Hao-yu; Khurwolah, Mohammad Reeaze; Liu, Jia-bao; Tang, Heng; Aa, Nan; Yang, Zhi-jian
Abstract: Background and purpose: Stable angina pectoris is a common symptom imperiling patients' life quality. The purpose of this meta-analysis is to assess the effectiveness of acupuncture alone or acupuncture plus medicine for the treatment of stable angina pectoris. Methods: Seven databases were searched ranging from 1959 to February 2018. Quantitative analysis of randomized controlled trials (RCTs) was performed by RevMan 5.3 software and STATA 12.0 program, and Cochrane criteria for risk-of-bias was used to assess the methodological quality of the trials. Results: A total of 12 RCTs involving 974 patients were enrolled in this study. The pooled results showed that both acupuncture group (RR: 0.35, P < 0.00001; RR: 0.49, P < 0.00001) and acupuncture plus medicine group (RR: 0.26, P < 0.00001; RR: 0.52, P = 0.03) were associated with a higher percentage of improved anginal symptoms as well as electrocardiographic (ECG) results compared to medicine group. The acupuncture plus medicine group also had a lower intake rate of nitroglycerin than medicine group (Non-event RR: 0.79, P = 0.03). However, there was no significant difference in the reduction or discontinuation of nitroglycerin intake between acupuncture group and medicine group. No acupuncture-related adverse effects were observed or reported in the included trials. Conclusion: Acupuncture therapy may improve anginal symptoms and ECG results in patients with stable angina pectoris, and can serve as an adjunctive treatment for this condition. Highlights: The first study to assess the effectiveness of acupuncture or acupuncture plus medicine for treatment of stable angina. Our updated meta-analysis provided new evidence of acupuncture therapy for stable coronary artery disease. Acupuncture may improve angina symptoms and ECG results of patients with stable angina pectoris. Acupuncture therapy may be an additionally effective treatment for stable angina pectoris.